2021
DOI: 10.48550/arxiv.2112.11604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of axion-like particles via vector boson fusion at future electron-positron colliders

Chong-Xing Yue,
Hua-Ying Zhang,
Han Wang

Abstract: One kind of particularly interesting pseudoscalar particles, called axion-like particles (ALPs), have rich physical phenomenology at high-and low-energy collider experiments. After discussing most of single production channels of ALP at electron-positron colliders, we investigate the possibility of detecting this kind of new particles through the W + W − fusion process e + e − → ν e ν e a (→ γγ) at the CLIC. The 3σ and 5σ bounds on the ALP parameter space at the three energy stages of the CLIC are obtained. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Recent phenomenology studies on ALPs at e − e + colliders can be found in Refs. [44][45][46][47][48][49], and more studies can be found in the reviews [50][51][52][53][54][55] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Recent phenomenology studies on ALPs at e − e + colliders can be found in Refs. [44][45][46][47][48][49], and more studies can be found in the reviews [50][51][52][53][54][55] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Another search constrains the ALP-gluon-gluon coupling through the signal process gg → a → ZZ, Zh at the LHC by the CMS collaboration [31]. Additionally, a plethora of phenomenological researches [19,[33][34][35][36][37][38][39][40][41][42][43][44] have also been amassed on the sensitivities of the ALP-gluon-gluon coupling, albeit dominantly in the sub-GeV ALP mass range.…”
Section: Introductionmentioning
confidence: 99%